The Novel Non-coding Transcriptional Regulator Gm18840 Drives Cardiomyocyte Apoptosis in Myocardial Infarction Post Ischemia/Reperfusion - Luo, Changjun; Xiong, Si; Huang, Yiteng; Deng, Ming; Zhang, Jing; Chen, Jianlin; Yang, Rongfeng; Ke, Xiao (Frontiers in Cell and Developmental Biology, 2021)
Background: Ischemia/reperfusion -mediated myocardial infarction (MIRI) is a major pathological factor implicated in the progression of ischemic heart disease but the key factors dys-regulated during in the MIRI remains unclear, especially those essential non-coding factors required for cardiovascular development. Methods: The murine MIRI model and RNA sequencing (RNA-seq) were used to identify key lncRNAs after myocardial infarction. qRT-PCR was used to validate expression in cardiac muscle tissues and myocardial cells. The role of Gm18840 in HL-1 cell growth was determined by flow cytometry experiments in vitro. The full-length of Gm18840 was identified by using Rapid amplification of cDNA ends (RACE) assay. Subcellular distribution of Gm18840 was examined by nuclear/cytoplasmic RNA fractionation and qRT-PCR. RNA pull-down and RNA Immunoprecipitation (RIP)-qPCR assays were performed to identify Gm18840-interacted proteins. The ChIRP-seq (Chromatin Isolation by RNA purification) was used for identifying the genome-wide binding of Gm18840 on chromatin. The regulatory activity of Gm18840 in transcriptional regulation were examined by luciferase reporter assay and qRT- PCR. Results: Gm18840 was upregulated post the myocardial infarction in both in vivo and in vitro MIRI models. Gm18840 was defined to be 1471 nt in length and localized in both cytoplasm and nucleus of HL-1 cells. Functional studies shown that knockdown of Gm18840 promoted the apoptosis of HL-1 cells. Gm18840 directly interact with the histones, including the H2B, highlighting a potential function on transcriptional regulation. Further ChIRP-seq and RNA-seq analyses shown that the Gm18840 directly bound at the cis-regulatory regions of genes involved in development processes, such as Junb, Rras2 and Bcl3. Conclusions: Gm18840, a novel transcriptional regulator, promoted apoptosis of myocardial cells via direct transcriptional regulation of genes essential for might serve as a novel therapeutic target for MIRI .